2010
DOI: 10.1111/j.1467-8691.2010.00581.x
|View full text |Cite
|
Sign up to set email alerts
|

Ideation Capabilities for Continuous Innovation

Abstract: This paper explores ideation capabilities in large organizations. Based on the dynamic capabilities framework, it is seen that ideation capabilities are managerial and organizational processes for the stimulation, identification, selection and implementation of ideas. In order to explore how these capabilities are manifested and used in firms, case studies of four Swedish companies have been performed. The results of the study show that there are different approaches to ideation. In terms of the nature of inno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
13

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 36 publications
0
61
0
13
Order By: Relevance
“…Geração de ideias é o processo sistemático de criar e captar ideias de acordo com os requisitos definidos pela organização, e compreende elementos relativos à criatividade e elementos relativos à estrutura organizacional para apoiar o processo (FLYNN BJÖRK, 2010;COOPER, 2011). Girota, Terwiesch e Ulrich (2010) afirmam que praticamente todos os processos de inovação incluem a geração de ideias e a seleção de oportunidades ou ideias.…”
Section: Geração De Ideiasunclassified
“…Geração de ideias é o processo sistemático de criar e captar ideias de acordo com os requisitos definidos pela organização, e compreende elementos relativos à criatividade e elementos relativos à estrutura organizacional para apoiar o processo (FLYNN BJÖRK, 2010;COOPER, 2011). Girota, Terwiesch e Ulrich (2010) afirmam que praticamente todos os processos de inovação incluem a geração de ideias e a seleção de oportunidades ou ideias.…”
Section: Geração De Ideiasunclassified
“…It was also found that many authors represented on the chart publish together, for example: E. F. Rietzschel, B. A. Nijstad and W. Stroebe (Nijstad et al, 2002;Rietzschel et al, 2006Rietzschel et al, , 2009Rietzschel et al, , 2010; J. Björk and M. G. Magnunsson (Björk & Magnunsson, 2009;Björk et al, 2010;; and J. S. Linsey and K. L. Wood (Hey et al, 2008;Linsey et al, 2008;Linsey et al, 2011).…”
Section: Bibliometric Datamentioning
confidence: 97%
“…Based on the concept of ideation capabilities as managerial and organizational processes for stimulation, identification, selection and implementation of ideas, Björk et al (2010) study four Swedish companies with a focus on the ideation approach used by them. The authors found out that different approaches are used, and pointed out the difficulties encountered by companies with respect to: the degree of formalization of the process; the extent of involvement of employees; and the degree of deliberate pursuit of ideas.…”
Section: Idea Management Processesmentioning
confidence: 99%
“…Se a empresa impuser uma direção em excesso, pode estreitar a busca por inovações. Se deixar a geração de novas idéias depender de um processo mais informal de trabalho, correrá o risco da ineficiência pela falta de controle (Björk, Boccardelli, & Magnusson, 2010).…”
Section: Introductionunclassified